Reading between the lines: The necessity of books (Journal of Applied Learning and Teaching, 2024)
This opinion piece delves into the unwavering significance of books as an enduring and robust medium of education. It traces the historical trajectory of books, from ancient scrolls to contemporary printed volumes, elucidating their consistent role in education and knowledge dissemination. Books serve as indispensable repositories of human wisdom, culture, and progress, preserving the intellectual heritage of bygone eras and steering society toward enlightenment. Amidst the digital age’s proliferation of screens and electronic devices, this paper argues that books in the physical form maintain their charm, captivating readers and learners alike. Their tangible presence and tactile engagement provide a unique haven for knowledge seekers, serving as steadfast companions in the lifelong pursuit of learning. In an era marked by rapid technological advancement, books stand as a testament to the enduring worth of written knowledge. As we embrace innovation, it is crucial to acknowledge the timeless wisdom contained within books’ pages, forever prepared to guide us on our journey to comprehension and enlightenment.